Nutrient content in dadiah pudding, a potential source of probiotics from Minangkabau, West Sumatra - Zuhrah Taufiqa; Dian Novita Chandra; Nur Indrawaty Lipoeto; Badriul Hegar (Majalah Kedokteran Andalas, 2024)
Introduction: Dadiah is a fermented milk product derived from the milk of West Sumatran swamp buffaloes.  Methods: The manufacture of dadiah pudding used dadiah fermented milk obtained from Bukittinggi, West Sumatra. Levels of carbohydrate, protein, fat, calcium, zinc, and iron were measured according to the Indonesian National Standard, then total calories were determined using 4:4:9 kcal/g conversion. Inoculation of samples on de Man, Rogosa, and Sharpe agar was performed to determine total lactic acid bacteria counts, and Gram staining was done for further morphological confirmation. Results: The result revealed that 100 g dadiah pudding contained 6.49 g of carbohydrates, 6.12 g of protein, 23.31 g of fat, 260.23 kcal of calories, 276.61 mg of calcium, 3.75 mg of zinc, 6.60 mg of iron, and 6.1 × 10⁹ CFU/ml of lactic acid bacteria assuming that modification of the liquid into pudding form has been shown to impact macronutrient, micronutrients, total calories, and total lactic acid bacteria. Conclusion: The nutrient content in dadiah pudding revealed in this study indicates that this dairy product can be used as a nutritious local food source and a potential probiotic.